Climate Change, the Quadrilemma of Globalization, and Other Politically Incorrect Reactions. Issue 6 (1st November 2016) - Gudynas, Eduardo
Abstract: Current global climate change negotiations face some contradictions that are not always addressed as they are considered politically incorrect. These include, first, the decoupling of commitments for planetary environmental policies with the actual national strategies. A relevant example is the Bolivian administration, which presents a strong rhetoric for biospheric Mother Earth Rights, but its national development strategies generate more environmental impacts and weaken enforcement at the local level. Second, the core ideas and beliefs that explain development varieties that generate climate change are deeply rooted, so changes in political ideologies, either from traditional 'left' or 'right', do not determine policies to effectively overcome climate change. Third, accumulation of scientific information is not enough to promote the necessary changes, because these deep roots conditioned perceived and acceptable alternatives. Fourth, this lead to tensions among the pursuit of economic financial globalization, the sovereignty of the nations-states, democracy, and the basement of global environmental conservation. This is a quadrilemma, because if one or two of these objectives are pursued, at least one other is violated. Nevertheless, international negotiations rest on wishful thinking that this is possible. Uncovering these contradictions is politically incorrect for many realms.